A SWOT Analysis for Libraries of Shahid Beheshti University and Providing Appropriate Strategies - Dariush Matlabi; Parvaneh Pouriani javan; Mohsen Zeinolabedini (علوم و فنون مدیریت اطلاعات, 2021)
Aim: The increasing complexity of activities and the changing environment of today’s world have made managers face such difficulties that the slightest slip and their lack of attention to issues will have irreparable consequences. By using strategic planning, organizations can perform better and react to their environment properly and promptly. Developing strategies to determine the organization's major directions will provide guidelines to allocate resources toward long-term goals. Strategic planning analyzes the underlying environmental risk factors and provides solutions that are more likely to be appropriate to achieve the goal. Despite the importance of a strategic plan, its necessity is still not well understood in many organizations, and in some cases, it is even considered a luxurious and costly thing. The purpose of this study is to provide a strategic plan for Shahid Beheshti University Libraries. Methods: Analytical survey was used as a research method and is based on David’s strategic planning model and strategic planning factors (SWOT) technique. The statistical population consisted of all managers (8 people) and experts (45 people) of the Libraries of Shahid Beheshti University who were studied as a research community as ad census. A questionnaire and interview were used to collect data. Findings: The finding showed that the evaluation score of internal and external factors in libraries respectively was 3.11 and 3.3, which is more than the total average score (2.5); So in internal factors, strengths are more than weaknesses and in external factors, opportunities are more than threats. The most important strength was the "re-engineering of the various parts of the library", which led to the flexibility and modernity of the collection, as well as the attractiveness of the library space and the use of minimal space to achieve great goals; and the most important weakness was the "old and worn out parts of the library". "Attracting excellent students to the university" is the most important opportunity and "constantly changing policies and decisions related to libraries and its impact on changing the duties of librarians" is the most important threat to the libraries of Shahid Beheshti University. Results: The results showed that the main purpose of Shahid Beheshti University libraries providing information resources based on faculty members, students, and staff's needs of Shahid Beheshti University. Promoting research, education, and cultural activities and increasing specialized knowledge were in second and third rank; therefore, the libraries should consider 18 main strategies based on the proposed strategic plan.